A curious case of stress fracture in a transsexual athlete. (31st March 2016) - Richardson, Tom; Grant, Michael; Chandran, Prakash
Abstract : Femoral neck stress fractures in young healthy individuals are rare and occur in those who take part in physical training with repetitive loading and those with osteoporosis. Bone density is related to sex hormone status, which is artificially manipulated during gender reassignment. Conflicting evidence currently exists on the effect of cross sex hormone treatment on bone density, with no literature suggesting a link between hormone treatment in gender reassignment and stress fractures. Our aim is to highlight the potential risk of stress fractures amongst transsexual patients receiving cross sex hormones as part of gender reassignment. The patient presented with groin pain after competing in a running event. Despite a number of risk factors, there was a delay in diagnosis, which could have led to complications compromising outcome. Femoral neck stress fractures should be considered in the differential diagnosis of transsexual patients receiving hormone treatment with non-specific groin/thigh pain following exercise.